The brave little grork - Cave, Kathryn; Maland, Nick (London : Hodder Children's Books, 2002)
Two friends, one shy and easily frightened, and the other brave and fearless, do almost everything together. How does such an unlikely pair get along on an outing?
Keywords: Children's stories